Revealing the Genetic Mutation in a Diprosopus Monauchenos Calf - Pintaka Bayu Putra, Widya; Said, Syahruddin; Febyastri, Meda; Nanditya, Wisnu Krisna; Novita, Risqa (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
ABSTRACTDiprosopus Monauchenos (DM) is one of congenital defect that can be caused by a genetical factor. This study was conducted to reveal the genetic mutation of DM cattle. Research showed that along 354 bp of partial BTA13 sequence (69,985,393th - 69,985,745th nucleotide) in DM and normal samples were obtained by sequencing analysis. Research showed that one insertion/deletion (indel) mutation at 28th and two transition mutations at 241th and 269th positions were detected in both samples. The obtained sequence in the present study was located at the intronic region of LPIN3 gene (69,972,281th - 69,991,534th nucleotide). In the future, a depth research to investigate the genetic mutation in DM animal with whole genome analysis is important to get the results accurately.Keywords: cattle, DM, mutations, sequencing, BTA13